Sustainable Supply Chain Management. - Morana, Joëlle (Wiley-ISTE, 2013)
It is commonly recognized that logistics has become a major strategic issue for all companies, whether they are part of the primary, secondary or tertiary sector. Faced with the external pressures of globalization and competition, logistics optimizes processes and reduces production and delivery cycles. The use of Sustainable Supply Chain Management (SuSCM) is now increasingly at the center of thought, due to the numerous factors favoring its implementation: requests from various stakeholders, governmental pressures (decrees, laws, regulations, etc.), environmental pressures (pollution.
Keywords: Business logistics.; elektronické knihy; electronic books